Challenges in Addressing the Ethical Aspects of Artificial Intelligence to Detect Fraud in Public Procurement Processes - Sampaio, Igor Garcia Ballhausen; Bernardini, Flávia Cristina; Viterbo, José (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics), 2024)
Public Procurement Processes (PPPs) involve substantial taxpayer money, necessitating efficiency and transparency. Artificial Intelligence (AI) is increasingly applied to fraud detection in PPPs, enhancing these processes. This work presents a literature review on AI’s role in PPP fraud detection, focusing on ethical and technical challenges, including fairness, transparency, and privacy. We examine the global state of AI applications in PPPs, highlighting best practices and case studies. By analyzing these technologies’ challenges and opportunities, we provide insights and propose strategies for mitigating risks, contributing to the debate on responsible AI adoption in the public sector.